Learn Chinese : [videorecording (DVD)] : let's go to market in China - Qian, Jade (Follow Jade, 2003)
Jade incorporates basic Chinese words into everyday conversation about topics familiar to children. Topics include: body parts, fruits, farm animals, visiting a market, and clapping and stomping.